Decreased expression of villin has adverse effect on the prognosis of patients with colorectal cancer (Annals of Medical Research, 2021)
Aim: The expression of villin protein is widely used to determine to the gastrointestinal origin of metastatic tumors. However, little is known about the prognostic value of villin expression in colorectal cancer (CRC). The aim of this study is to investigate the relation between villin expression and basic histopathological features and survival in CRC. Secondarily, investigation of the prognostic significance of the CD4+/CD8+ TILs ratio was adopted.Materials and Methods: Villin expression and CD4+/CD8+ TILs ratio were evaluated in paraffin-embedded tumor tissues of 147 CRC patients, immunohistochemically.Results: Decreased villin expression was clearly detected in the tumoral areas compared to non-tumoral colonic mucosa. Loss of villin expression was closely related to high depth of tumor invasion (P = 0.001, ANOVA), increased lymph node metastasis (P
Keywords: Colorectal cancer; CD4 /CD8 TILs ratio; prognosis; villin